Group 2 innate lymphoid cells mediate ozone-induced airway inflammation and hyperresponsiveness in mice - Yang, Qi; Ge, Moyar Q.; Kokalari, Blerina; Redai, Imre G.; Wang, Xinxin; Kemeny, David M.; Bhandoola, Avinash; Haczku, Angela (Journal of allergy and clinical immunology, 2016)
Asthmatic patients are highly susceptible to air pollution and in particular to the effects of ozone (O3) inhalation, but the underlying mechanisms remain unclear. Using mouse models of O3-induced airway inflammation and airway hyperresponsiveness (AHR), we sought to investigate the role of the recently discovered group 2 innate lymphoid cells (ILC2s). C57BL/6 and BALB/c mice were exposed to Aspergillus fumigatus, O3, or both (3 ppm for 2 hours). ILC2s were isolated by means of fluorescence-activated cell sorting and studied for Il5 and Il13 mRNA expression. ILC2s were depleted with anti-Thy1.2 mAb and replaced by means of intratracheal transfer of ex vivo expanded Thy1.1 ILC2s. Cytokine levels (ELISA and quantitative PCR), inflammatory cell profile, and AHR (flexiVent) were assessed in the mice. In addition to neutrophil influx, O3 inhalation elicited the appearance of eosinophils and IL-5 in the airways of BALB/c but not C57BL/6 mice. Although O3-induced expression of IL-33, a known activator of ILC2s, in the lung was similar between these strains, isolated pulmonary ILC2s from O3-exposed BALB/c mice had significantly greater Il5 and Il13 mRNA expression than C57BL/6 mice. This suggested that an altered ILC2 function in BALB/c mice might mediate the increased O3 responsiveness. Indeed, anti-Thy1.2 treatment abolished but ILC2s added back dramatically enhanced O3-induced AHR. O3-induced activation of pulmonary ILC2s was necessary and sufficient to mediate asthma-like changes in BALB/c mice. This previously unrecognized role of ILC2s might help explain the heightened susceptibility of human asthmatic airways to O3 exposure.